Online radicalization: the net or the netizen? - Femi Richard Omotoyinbo (Social Technologies, 2014)
Purpose - Radicalization has gained some unusual prominence in the academic circles; maintaining a generic existence not only in the political sector. And with the advent of the Information Communication Technology (ICT), radicalization has begun to have some virtual dimension even in the remotest of human communities. This study seeks to mobilize a universal awareness on the collective urgency to oppose Online Radicalization (a radicalization that happens through the internet) due to its propensity to engendering conflicts. It also aims at identifying the principal cause of online radicalization and steer a clear course for a practical reversal in the systems of online radicalization. Design/methodology/approach - The study is divided into three primary parts. The general notion of radicalization is the focus of the first part; which is further analysed into the levels of online radicalization with its accompanying developments and segments. The second part utilizes analytic and historical method to pinpoint the principal cause of online radicalization amidst the suspected causal factors (the Net and the Netizen). The final part analytically focuses on the Netizen (a user/citizen of the internet) as the primary cause of online radicalization, and how the global community can bring about a corresponding change in the Net by the application of some measures on the Netizen. Findings - By virtue of the analytic plus historical methods employed by this study; it was initially identified that radicalization is basically having two versions which are online and offline. Further emphasis on the online version reveals that its existence is only made possible by the availability of the internet (the Net). Since the Net is a global phenomenon online radicalization is considered to be worldwide: a menace of globalization. However, the study later indicated that the Net is a facilitator and a cause of online radicalization. A view was deduced that the Netizen is of two categories that include the broad category and the jargon category. The Netizen in the former category was later on conceived as the principal cause of online radicalization. Research limitations/implications - The study averred that all attempts/measures to bring about a reversal in the status quo of online radicalization [De-Radicalization measures] should be directly applied to the principal cause, which is the Netizen. Although the content of the de-radicalization measures were not fully provided by this study due to the reason that the contents can best be supplied by almost everyone that has a vivid understanding of online radicalization. The study continues to affirm that the application of the measures of de-radicalization on the Netizen will bring a corresponding ameliorative effect on the Net against its perpetuation of online radicalization. Practical implications - It is important for domain name providers, governments, internet service providers, mass media, NGOs, parents, politicians, religious organisations, schools, teachers, and web hosting companies to collaborate to create practicable contents for a Gradual Online De-Radicalization (G.O.D) which will suppress the perturbing rate of Online Radicalization to the minimal. No unit or sector can singly tackle online radicalization effectively. Therefore, measures of De-Radicalization should be governed by international treaties and laws, and there should be credible agents to legislate and execute the laws respectively. Originality and value - This study broadens the possibilities of reducing online radicalization to the barest minimum globally with some novel strategies categorized broadly as Gradual Online De-Radicalization (G.O.D). The analytic methods applied were plausible skills from the realm of Philosophy and Science respectively. Thus, the findings and suggestions of this study are considered reasonable and universally pragmatic. Research type - general review and viewpoint.